An Exploration of Community Engagement and Participation in the Low Carbon City (LCC) Initiative: Case Study of Majlis Bandaraya Shah Alam - Yusfida Ayu, Abdullah; Khalid, Zanudin; Nor Baizura, Jamaluddin; Marlyana Azyyati, Marzukhi; Mohammad, Yusup (Malaysian Institute of Planners, 2023)
This research paper examines the state of community awareness and participation in the Low Carbon City (LCC) initiative by the Majlis Bandaraya Shah Alam (MBSA). The study aimed to explore the level of understanding, awareness, and involvement of the community in the low carbon city initiative, and to identify the factors that influence community participation. The study employed a qualitative approach where focus group discussions involving key stakeholders were conducted, and subsequently, thematically analysed. The findings suggest that the level of community awareness and participation in the low carbon city initiatives in Shah Alam is relatively low. Factors such as participation and information-sharing methods, and a lack of collaboration between stakeholders were identified as barriers to community participation. The study recommends that MBSA prioritises community engagement and education, including best practices, to increase community awareness and participation. In addition, the methods for participation and information sharing should be tailored to the target group. The findings also suggested continuous discussion and engagement among the stakeholders, especially between the communities and the local authority, can promote active participation in the LCC initiatives among the communities in Shah Alam.